Pengaruh Biaya Lingkungan dan Environmental, Social and Governance Disclosure terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening : Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Yanti Zalsabila; Muh. Akob Kadir; Asbi Amin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine and analyze the effect of environmental costs and Environmental, Social, and Governance (ESG) disclosure on firm value with financial performance as an intervening variable in mining sector companies listed on the Indonesia Stock Exchange. The research method uses a quantitative approach with SmartPLS analysis techniques. The population consists of 42 mining companies listed on the IDX in 2022–2024, with a sample of 36 financial reports and annual reports determined through purposive sampling. The results show that environmental costs have no effect on financial performance, as they are considered more of a compliance cost that does not increase short-term profitability. ESG disclosure has no effect on financial performance since investors still focus on traditional financial indicators. Environmental costs have no effect on firm value, as they are perceived as a burden that reduces profit prospects. ESG disclosure has no effect on firm value, even though it is important for reputation and social legitimacy. Financial performance has no effect on firm value because it is more strongly influenced by external factors such as commodity prices, regulations, and environmental issues. Furthermore, environmental costs have no effect on firm value through financial performance as an intervening variable, and ESG disclosure also has no effect on firm value through financial performance as an intervening variable. Theoretically, this study contributes to the literature on the effect of environmental costs and ESG disclosure on firm value with financial performance as an intervening variable. Practically, the results can serve as a reference for companies in managing sustainability strategies more effectively and for future researchers in developing related studies.